The use of CPT to evaluate the effect of helical pile installation in tropical soils - Santos, T. C.; Tsuha, C. H C; Giacheti, H. L. [UNESP] (My University, 2013)
The uplift capacity of helical piles depends on the shear resistance of the soil above the helical plates. During helical pile installation, the soil traversed by the plates are sheared and displaced laterally, and consequently the soil structure is disturbed. Considering this fact, the aim of this paper is presenting the effect of helical piles installation in the soil mass by means of CPT tests carried out close to the soil cylinder above the pile helices. The CPT tests were performed at the CRHEA site from the Sao Carlos School of Engineering, Sao Carlos city, inland of Sao Paulo State, Brazil. In addition, an interpretation of CPT tests data for stratigrafic logging are presented and compared to Standard Penetration Tests (SPT) carried out at this site. This study showed that the CPT sleeve friction fs data were affected by the installation of helical pile in this particular tropical soil site. © 2013 Taylor & Francis Group.
Keywords: CPT test; Helical pile; Tropical soils; Pile installation; Sao Paulo; School of engineering; Shear resistances; Sleeve friction; Soil mass; Soil structure; Standard penetration test; Uplift capacity; Characterization; Pile foundations; Piles; Plates (structural components); Tropics; Soils